Rising Metals Concentration in the Environment: A Response to Effluents of Leather Industries in Sialkot - Khalid, Noreen; Rizvi, Zarrin Fatima; Yousaf, Nousheen; Khan, Shujaul Mulk; Noman, Ali; Aqeel, Muhammad; Latif, Komal; Rafique, Asmara (Bulletin of environmental contamination and toxicology, 2021)
Many leather processing industries in Sialkot, Pakistan, discharge their wastes freely into the environment which then enters nearby water bodies. Irrigation practices with these polluted waters pose a great threat to the soil quality. Hence, the soils and effluent waters of five famous leather processing sites were evaluated for the presence of As, Cr, Cd, Ni, Zn, Mn, Mg, Na, K, and Ca. High mean concentrations of As (112.6 mg kg −1 ), Cr (45.9 mg kg −1 ), Cd (2.0 mg kg −1 ), Ni (58.2 mg kg −1 ), Zn (117.6 mg kg −1 ), Mn (12.8 mg kg −1 ), Mg (34,511 mg kg −1 ), Na (16,292 mg kg −1 ), K (1765 mg kg −1 ), and Ca (4387 mg kg −1 ) were found in soils at our study sites. Effluents were found to be highly acidic with high TDS content and high EC values. Index of Geoaccumulation ( Igeo ) confirmed the extremely toxic nature of these soils. Plants growing at these sites also showed high concentrations of As, Cr, and Cd in their leaves.